CORELATION OF PARENTS' PROFILES OF CHILDREN WITH LATE CLEFT REPAIR IN SURABAYA CLEFT LIP AND PALATE CENTRE (JANUARY 2015–DECEMBER 2017) - Laras Puspita Ningrum; Iswinarno Doso Saputro; Lobredia Zarasade (Jurnal Rekonstruksi dan Estetik)
Highlights: